Ichtyophagoi, their culture and economy: Survey and excavation in wadi bani khalid (WBK1, aqr zaida al athri) and tiwi - Loreto, Romolo (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Project’s activities in the Sultanate of Oman, Ash-Sharqiyah North region, are directed towards the study of the Iron Age in northern Oman, in order to investigate those historical cultures known as fish-eating communities (Ichtyophagoi) from Greco-Roman sources and locally defined as Early to Late Iron Age cultural facies. From 2014 to 2018 the project focused on the study of the seasonal coastal economy of northern Oman in the Iron Age, in particular the phases of the 1st millennium BCE, between Qurayat and Ras Al Hadd, including Bamah and Tiwi as main coastal sites. Since 2018, the joint project has extended the area of research to urban oases further inland, along the Al Hajar mountain range, to define the settlement strategies between the Iron Age and the advent of Islam. These seasonal villages were in fact part of a complex socio-economic network involving the urban and agricultural oases in the interior, located along the Al Hajar mountain range, possessing their own hunting/fishing, farming and livestock economies, acted as bridges for trade between the coasts and the more inland regions, between Oman and the Emirates for at least the entire first half of the 1st millennium BCE and from the 1st century BCE to the 4th century CE.
Keywords: Archéologie -- Oman